A pseudotargeted peptidomics strategy for screening natural signature peptides in animal-derived drugs: Taking Pheretima as a case - Dongdong Huang; Xiaoxiao Luo; Qirui Bi; Yelin Ding; Yun Li; Cuicui Wang; Min Gao; Yong Huang; Changliang Yao; Jianqing Zhang; Wenlong Wei; Yurong Wang; et al. (Arabian Journal of Chemistry, 2023)
Natural peptides (NPs) are ubiquitous throughout the organism with diversified structures and wide dynamic concentration range, which leads to serious challenge for their comprehensive analysis. Herein, a pseudotargeted peptidomics strategy based on dynamic multiple reaction monitoring (DMRM) with high-throughput data acquisition and accurate quantification was established. Specifically, an in-house software Pep-MRMer was developed for extraction of ions information of peptides, followed by de-redundancy and fusion to construct a transition list. Additionally, retention time (RT) calibration method was optimized by using high content components for effective transference of ion pairs between different detection conditions (e.g., instruments, chromatographic gradients). This strategy was applied for profiling NPs and screening signature peptides for species authentication of Pheretima, a multi-source animal-derived drug widely used in Asian countries. In all, a total of 3307 peptides had excellent quantitative detection after transference. Subsequently, nine signature peptides with extraordinary specificity were screened, identified, and confirmed by comparing with the synthetic standards. Ultimately, a 10 min specific chromatogram based on signature peptides was developed, which realized rapid and accurate identification of Pheretima. Taken together, this research provides a robust strategy for species discrimination of animal-derived drugs without adequate quality control measures.